2021
DOI: 10.1080/19401493.2021.1908427
|View full text |Cite
|
Sign up to set email alerts
|

A hybrid system of data-driven approaches for simulating residential energy demand profiles

Abstract: This paper presents a novel system of data-driven approaches for simulating the dynamics of electricity demand profiles. Demand profiles of individual dwellings are decomposed into deterministic (e.g. 'Trends' and 'Seasonal') and stochastic ('remainder') components using the STL (a Seasonal-Trend decomposition procedure based on Loess) approach. Stochastic components are modelled using a Hidden Markov Model (HMM) and combined with deterministic components to generate synthetic demand profiles. To simulate extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Thus, the HMM_GP framework is shown to effectively simulate the dynamics of the climatic variable along with river runoff. In fact, in earlier work by the authors, the proposed modelling schematic was shown to generate statistical synthetics time series for a range of applications including energy demand series at different resolution in the range of 5-30 min [58] and for Scottish rivers inflow sequences (15 min inflow) [17]. In the present work, the model is first applied to simulate the statistical dynamics of climatic variables, then a novel climate module is developed.…”
Section: Calibration Of the Hmm_gp Model For Simulating Synthetics Sequencesmentioning
confidence: 99%
See 3 more Smart Citations
“…Thus, the HMM_GP framework is shown to effectively simulate the dynamics of the climatic variable along with river runoff. In fact, in earlier work by the authors, the proposed modelling schematic was shown to generate statistical synthetics time series for a range of applications including energy demand series at different resolution in the range of 5-30 min [58] and for Scottish rivers inflow sequences (15 min inflow) [17]. In the present work, the model is first applied to simulate the statistical dynamics of climatic variables, then a novel climate module is developed.…”
Section: Calibration Of the Hmm_gp Model For Simulating Synthetics Sequencesmentioning
confidence: 99%
“…Further details on snowmelt runoff for the Beas basin can be found elsewhere [57]. The methodological framework of the HMM_GP model consists of four stages and is illustrated in Figure 2, as adapted from [58]. The colour schematics applied in Figure 2 represent the key four stages of the HMM_GP modelling framework which are briefly described below and can found elsewhere [58] for underlying technical details.…”
Section: River Runoff Precipitation and Evapotranspiration Datamentioning
confidence: 99%
See 2 more Smart Citations